Potential role of proprietary patent medicine vendors in primary eye and ear care: A mixed methods study in northern Nigeria - Joseph Okeibunor; Andrew Smith; Emma Jolley; Elizabeth Elhassan; Oluwatosin Adekeye; Lawal Hasfat Kontagora; Sunday Isiyaku; William Adamani; Caleb Mpyet; Hannah Faal; Elena Schmidt; Clare E. Gilbert (PLoS ONE, 2025)
Background In Nigeria, patent and proprietary medicine vendors (PPMVs) are permitted to sell a limited range of medication. They are important providers of health care despite their limitations and may be trained to manage specific conditions, such as malaria, but not ear and eye conditions. In this study, PPMV’s knowledge and management of ear and eye problems and community members health seeking behaviour were explored, as well as whether community members would access PPMVs if they were trained in primary ear and eye care. Methods Quantitative and qualitative methods were used in a cross-sectional observation study: a survey of 1,591 adults in 40 clusters in two urban and two rural areas; 64 focus group discussions with community members and four with health professionals in two ear, nose, throat and eye clinics; in-depth interviews with ten community leaders, 11 primary health care workers, and 21 hospital staff. A check list was used to assess 36 PPMVs’ facilities and structured questionnaires were administered to 36 PPMVs and 401 hospital patients in ear and eye outpatient departments. Results Community members reported that eye and ear problems were frequent but less common than other conditions. Health seeking behaviour was influenced by accessibility, availability, cost of medication, and trust in the provider. Most PPMVs had no formal training, had little knowledge of ear and eye conditions and were enthusiastic about being trained to manage them. Living far (>5km) from a health facility, being male, uneducated and poor were significantly associated with willingness to access PPMV after training in primary ear or eye care. Conclusions PPMVs might be able to play a role in delivering primary ear and eye health care for common conditions, in collaboration with local clinicians. To do this, PPMVs would require training in eye and ear conditions and skills in their detection and counselling clients as well as reliable supply chains for medication, and skills in stock control, record keeping and facility management.